ANTIBACTERIAL ACTIVITY OF SEA GRAPES (Caulerpa racemosa) AGAINST Streptococcusmutans AND Shigella dysenteriae - Sri Hainil; Hesti Marliza; Maria Yunivista; Rastria Meilanda (JURNAL KATALISATOR, 2023)
The Riau Islands are known as an island group in Indonesia that is famous for its wealth of marine plants. Among the prominent marine flora, sea grape (Caulerpa racemosa) is a marine plant that produces secondary metabolites including alkaloids, saponins, phenolics, and flavonoids which have been proven to have antibacterial properties. Previous research showed that 70% ethanol extract from sea grapes exhibited strong antibacterial activity. However, there is no detailed information regarding the ability of the n-hexane and ethyl acetate fractions of sea grapes as antibacterials. This study aims to examine the antibacterial effects of n-hexane and ethyl acetate fractions from sea grapes against Streptococcus mutans and Shigella dysenteriae. The sea grape extraction process is carried out through the maceration method using 95% ethanol solvent, followed by the fractionation stage using the liquid-liquid extraction method. This fractionation process involves the use of non-polar (n-hexane) and semi-polar (ethyl acetate) solvents. The test method used was disk paper diffusion with varying fraction concentrations: 500 μg/disc, 400 μg/disk, 300 μg/disc, and 200 μg/disk. The positive control for this study used 30 μg/disc of tetracycline, because tetracycline is known as a broad-spectrum antibiotic. Meanwhile, the negative control used 10% DMSO. Findings from the research stated that the n-hexane fraction could not stop the growth of Streptococcus mutans bacteria, while the ethyl acetate fraction was able to inhibit the development of these bacteria. The average diameter at a concentration of 500 μg/disk was 9.2 mm, 400 μg/disk is 8 mm, 300 μg/disc is 7.7 mm, and 200 μg/disc is 6.5 mm. However, neither the ethyl acetate nor n-hexane fractions showed an inhibition zone against Shigella dysenteriae bacteria